The Estimation of the Antioxidant Enzymes Activity in Representatives of Different Populations of Lymnaea stagnalis Differ in the Degree of Infestation Under Temperature Stress - Axenov-Gribanov D.V.; Khomich A.S.; Bodilovskaya O.A.; Kondratieva E.S.; Lubyaga Y.A.; Shatilina Z.M.; Emshanova V.A.; Golubev A.P. (Journal of Stress Physiology & Biochemistry, 2016)
The aim of this study was to assess the impact of effects of thermal stress and parasitic infestation on the activity of antioxidant enzymes (peroxidase, catalase and glutathione S-transferase) in different populations of wide-spread species of pulmonate mollusk Lymnaea stagnalis from water bodies with different levels of anthropogenic pollution in Belarus - unpolluted Narach Lake and polluted Chizhovsky reservoir. There are several differences were found under thermal stress exposition (35 °С). In non infected mollusсs of both populations the peroxidase activity decreased and activity of catalase increased. An activity of glutathione S-transferase increased in non infested mollusks that inhabit polluted Chizhovsky reservoir.